Effective Digital Marketing Strategies in the Technology Era - Syarif, Roshanita; Nurhidayah, Nurhidayah; Kamaruddin, Syamsu A. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Background: In an increasingly competitive digital era, digital marketing strategies are the key to increasing a company's competitiveness. Digital media platforms must be able to be utilized by companies more effectively in order to reach a wider audience and have closer networks with consumers. This research aims to identify effective digital marketing strategies in increasing company competitiveness in the digital era. By understanding the latest trends and technology in digital marketing, companies can develop strategies that are more focused and responsive to the rapidly changing business environment. Method: This research uses a literature review method to collect and analyze various literature related to effective digital marketing strategies. Results: Digital marketing is a key element in modern marketing strategies. The use of digital platforms and media is able to reach audiences effectively. The lives of consumers are starting to experience a paradigm shift, triggering a consumer mindset that is all connected digitally, using mobile first, the internet and social media to search for information about a product brand digitally before making a purchase. Various uses of an effective digital marketing strategy are increasing brand visibility, expanding market reach, increasing consumer engagement, and optimizing user experience. Digital marketing trends continue to grow, with the use of social media, video-based content, AI, and machine learning as factors or influencing the way companies market their products or services.